(untitled) (Research, Society and Development, 2025)
This work aims to review the literature on the use of artificial intelligence (AI) in the planning of dental aesthetic treatments, with an emphasis on the ethical aspects involved. Artificial intelligence (AI) has promoted significant advances in Dentistry, especially in aesthetic procedures, by enabling more accurate diagnoses and personalized treatment planning. However, its growing use raises relevant ethical questions, particularly regarding professional autonomy, technical responsibility, and the protection of patient data. Based on the analysis of recent publications, including the work of "Oliveira", it is observed that although AI represents great potential for innovation in clinical practice, there are still gaps in the ethical training of professionals and students in the field. It is concluded that the responsible use of AI in Dentistry requires not only technical knowledge but also a solid understanding of the ethical principles that should guide its application.